Effects of insecure attachment on fMRI resting state functional connectivity in poly drug use disorder - Jürgen Fuchshuber; Karl Koschutnig; Andreas Fink; Johanna Alexopoulos; Henriette Löffler-Stastka; Human-Friedrich Unterrainer (PLoS ONE, 2025)
Background Insecure adult attachment has previously been linked to more severe psychopathology and to alterations within neuronal connectivity on a structural as well as functional level. Little is known about the resting state functional connectivity (rs-FC) of the attachment system in patients suffering from poly-drug use disorder (PUD). Methods The present study investigated rs-FC at two measuring points (t1: ROI-to-ROI; t2: seed-to-voxel) in a sample of PUD patients (n = 33; Age: M = 30y; SD = 8y; Female = 15%). Adult attachment was measured with the German version of the Experiences in Close Relationships Scale (ECR-RD8). Furthermore, insecure attachment was correlated with depressive symptoms (ADS), trait anxiety (STAI) and general psychopathology (BSI-53). Results More insecure attachment was associated with increased trait anxiety, depressive and general psychiatric symptom burden in patients. Furthermore, we observed time-stable links between insecure adult attachment and increased rs-FC between the left lateral parietal default mode network (DMN LP) and bilateral parts of the salience network, as well as decreased rs-FC between DMN LP and medial parts of the DMN. Discussion Implications of the present study are highlighting the association between attachment security and brain areas related to affect regulation.